THE EMOTIONAL IMPACT ON ADOLESCENTS DURING THE PANDEMIC SUBSTANTIATION FROM THE PERSPECTIVE OF SOCIO-EMOTIONAL AND SPIRITUAL INTELLIGENCES - Emil LAZĂR (Universitaria Publishing House, Craiova, 2021)
Training and development during adolescence are the main activities, with effects/ consequences/ benefits on the entire personality and with projections for the adult life of the human person. This paper aims to answer the question related to the relationship between emotional and spiritual intelligence of the high school teenagers, pursuing other educational aspects influenced by the consequences of this relationship (behaviours, habits and school adjustment).